Revision of the South American Ceratognathini (Coleoptera: Lucanidae: Aesalinae) with the description of a new genus and a new species - Paulsen, M. J.; E., José Mondaca (Zootaxa, 2006)
We examine the taxonomic placement of the South American stag beetles of the tribe Ceratognathini Sharp, 1899 that were previously placed in the genus Ceratognathus Westwood. We compared the South American species with specimens from 13 species of Australasian Ceratognathini using morphological characters of the legs, mandibles, genitalia, and elytra. Based on generic limits proposed by Holloway for the Australasian Ceratognathini, the South American species differ from the three Australasian genera (Ceratognathus, Mitophyllus Parry, and Holloceratognathus Nikolajev) sufficiently to establish a new genus, Hilophyllus n. gen. The South American taxa are transferred to the new genus, resulting in two new combinations: Hilophyllus argentinensis (Martínez) and H. penai (Martínez). During our study of the Neotropical species we discovered a third species (H. martinezi, n. sp.), which is described here as new. To maintain nomenclatural stability we designate a neotype for H. argentinensis, the holotype of which is lost. The two previously known species of Hilophyllus are redescribed and a key to Hilophyllus species is provided.